Peningkatan Kompetensi Pelaku UMKM dalam Penyusunan Laporan Keuangan dengan Aplikasi Si Apik - Nugroho, Prayudi; Riyanto, Edy; Wirawan, Aditya (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2024)
Current development in number of MSMEs has not been matched by increase in quality of MSMEs, because some MSMEs still have problems recording and reporting financial transactions according to SAK, resulting in problems in applying for bank loans. Studies on several MSMEs in Tangsel show that problem occurs because of limited competence of MSME managers in field of financial accounting. To overcome this problem, community service activities were carried out by PKN STAN together with Bank Indonesia and Tangsel City Government, in form of socialization and training on the SIAPIK application, supported by visitations, assistance and consultations. This activity aims to make MSME managers able to understand and record financial transactions, to produce MSME financial reports in accordance with SAK with the help of SIAPIK application independently, and finally to be able to make economic decisions, especially regarding proposals for bank credit applications to improve and develop MSME businesses.